Accounting students’ motivation in classroom effects on their critical thinking and psychological well-being through edpuzzle and clear coaching - Danilah Salleh; Norhaiza Khairudin; Marhaiza Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
The capacity for rational and objective analysis, evaluation, and application of information is known as critical thinking. For accountants, who must base their decisions and judgments on financial data, rules, and laws, it is an essential talent. In terms of psychology, students' well-being is a dynamic concept that encompasses social, psychological, and subjective aspects in addition to health-related behaviors that arise from educational events that support students in their quest for meaning and guidance in life as well as assist them in realizing their full potential. This study aims to investigate if Edpuzzle and Clear Coaching tools improve students' motivation, which in turn leads to better critical thinking abilities and psychological health. The study was carried out in an accounting class utilizing the action research approach. The study involved thirty-five accounting students. According to the study, students with strong psychological health and critical thinking abilities behave more effectively and thoughtfully, pose more difficult questions, and engage fully in the learning process. This demonstrates that when teaching and learning are conducted with the appropriate resources, students' motivation can rise.